Alternaria brassicifolii sp. nov. Isolated from Brassica rapa subsp. pekinensis in Korea. Issue 2 (3rd April 2018) - Deng, Jian Xin; Li, Mei Jia; Paul, Narayan Chandra; Oo, May Moe; Lee, Hyang Burm; Oh, Sang-Keun; Yu, Seung Hun
Abstract: A new species belonging to the genus Alternaria was isolated from the necrotic leaf spots of Brassica rapa subsp. pekinensis in Yuseong district, Daejeon, Korea. It is an occasional isolate, not an etiological agent, which is morphologically similar to A. broccoli-italicae, but differs in conidial size and conidiophore shape. Phylogenetic analysis using the sequence datasets of the internal transcribed spacer (ITS) region of the rDNA, glyceraldehyde-3-phosphate dehydrogenase (gpd), and plasma membrane ATPase genes showed that it is distantly related to A. broccoli-italicae and closely related to Alternaria species in the section Pseudoalternaria, which belonged to a clade basal to the section Infectoriae . Morphologically, the species is unique because it produces solitary conidia or conidial chains (two units), unlike the four members in the section Pseudoalternaria that produce conidia as short branched chains. It exhibits weak pathogenicity in the host plant. This report includes the description and illustration of A. brassicifolii as a new species.